Composition of volcanic tephra, Haungaroa volcano - Alexander Diehl; Wolfgang Bach (PANGAEA, 2020)
XRF measurement of bulk rock composition of sample SO253-035-ROV15M recovered during RV Sonne expedition SO253 (Kermadec arc).